An analysis of single pole reclosing on 500 kV line in Thailand - K. Ngamsanroaj (2018)
This paper describes a study of single pole reclosing on 500 kV transmission lines in the Electricity Generating Authority of Thailand (EGAT) system. The work has been prepared to adopt for successful single pole reclosing. The paper covers area such as single-phase tripping, auto-reclosing, methods of secondary arc extinction and related system requirements. The EGAT 500 kV system is simulated. At the boundary of the simulation, the external grid was represented by positive/zero sequence equivalent impedances. All simulations were done with EMTP. Methods of reducing this secondary current are considered in this paper. © 2007 RPS.